2019
DOI: 10.1016/j.jconrel.2019.05.043
|View full text |Cite
|
Sign up to set email alerts
|

Local inflammation alters the lung disposition of a drug loaded pegylated liposome after pulmonary dosing to rats

Abstract: The development of inhalable 'nanomedicines' based on biocompatible lipids and polymers is attracting increasing interest worldwide. Our understanding of how pulmonary inflammation impacts on lung distribution and clearance kinetics however, is limited. Similarly, there is limited information on how the inhaled delivery of biocompatible nanomaterials affects existing respiratory disease. We have addressed these knowledge gaps by describing and comparing the pulmonary pharmacokinetic behaviour of a 3 H-labelled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 47 publications
1
16
0
Order By: Relevance
“…The niosomal formulation appears to concentrate at these organs and was able to reduce viable bacterial counts more efficiently than the conventional unentrapped drug. These results are similar to various studies done with a liposomal drug delivery system [ 28 30 ].…”
Section: Discussionsupporting
confidence: 92%
“…The niosomal formulation appears to concentrate at these organs and was able to reduce viable bacterial counts more efficiently than the conventional unentrapped drug. These results are similar to various studies done with a liposomal drug delivery system [ 28 30 ].…”
Section: Discussionsupporting
confidence: 92%
“…The plasma pharmacokinetics of 3 H-phosphatidylcholine revealed higher liposomal bioavailability and more prolonged absorption from inflamed lungs. Concentrations of the pro-inflammatory cytokine IL-1β were increased in bronchoalveolar lavage fluid after a single pulmonary dose of liposomes to rats with inflamed lungs, but no other significant changes in inflammatory lung markers were identified in healthy or bleomycin-challenged rats [ 24 ]. Moreover, inhaled drugs are also drained by the lymphatic system; they were commonly detected in the lungs’ lymph nodes ( Figure 1 ).…”
Section: Inhalable Anticancer Therapy Via Lipid-based Nanocarriers: Main Advantages and Critical Challengesmentioning
confidence: 99%
“…This was likely due to the very short time between LPS challenge and euthanasia of the animals (3 h). Previous work has demonstrated that it can take between 24–72 h for cytokine levels to peak in pulmonary instilled animals [ 39 , 61 ]. This was the case for CXCL-1 expression in all animals, with the exception of the PEI-LPEG NT siRNA-treated animals.…”
Section: Discussionmentioning
confidence: 99%